Problem Based Learning Using Open Ended Questions Improves Students’ Mathematical Critical Thinking Ability in Elementary Schools - Dwijayanti, Anak Agung Sagung Sinta; Wiarta, I Wayan (Thinking Skills and Creativity Journal, 2024)
Primary school students' critical thinking abilities in mathematics are still very low. This is caused by teachers who only provide learning with rote concepts without any problem solving activities. Based on this problem, a learning model is needed that can help students learn the concept of problem solving in mathematics. So research was conducted which aimed to prove the effect of the Problem Based Learning model using Open-Ended Questions on critical thinking skills in class III students' mathematics learning. This research uses a non-equivalent control group research design. The population of this research was 324 students. The research sample was 31 students as the experimental group and 29 students as the control group. Data collection methods and instruments were obtained by giving essay tests. Data analysis uses descriptive statistical techniques and inferential statistical analysis with polled variance t-test. The results of the hypothesis test show that the Problem Based Learning learning model using Open-Ended Questions has an effect on critical thinking skills in mathematics learning for third grade elementary school students. The results of the research carried out provide a good contribution to mathematics learning in elementary schools. It is hoped that the results of this research can be used to develop future research ideas.